Role of Vitamin D in Children with Respiratory Tract Infection. (January 2013) - Esposito, S.; Baggi, E.; Bianchini, S.; Marchisio, P.; Principi, N.
It has recently been shown that vitamin D (VitD) plays an important role in host defences, inflammation and immunity. We reviewed PubMed and selected all of the studies published over the last 15 years concerning VitD deficiency and VitD supplementation in children with respiratory tract infections. Our analysis showed that VitD seems to be very important because of its part in the complexity of the immune system. However, there are few pediatric studies and most have various limitations. First of all, the literature mainly refers to studies concerning the prevalence of VitD insufficiency and deficiency in specific pathologies. Secondly, it is extremely difficult to identify a common specific range of normal, insufficient and deficient VitD levels. Thirdly, the available studies of VitD supplementation often combined VitD with the use of other micronutrients, thus obscuring the role of VitD itself. Finally, different doses have been used for VitD supplementation. These observations clearly highlight the fact that further studies are needed to evaluate the impact of VitD deficiency and insufficiency in terms of the epidemiology and outcomes of pediatric respiratory tract infection, and whether VitD supplementation favours a positive outcome.